Evaluation of a State-Owned South African Oil Refinery’s Maintenance Strategy Selection Process and its Performance Effectiveness - Nqandela, A.; Peach, R.H. (The South African Journal of Industrial Engineering, 2025)
The ageing infrastructure at a state-owned South African petroleum refinery has led to frequent equipment breakdowns and increased downtime, shifting maintenance from preventive to reactive. This study investigates the most suitable maintenance strategy for nitrogen compressors, which are essential for purging and pressurising reactor systems. Using structured questionnaires and analysing the responses through frameworks such as reliability-centred maintenance (RCM), total productive maintenance (TPM), and risk management theory, the study identifies critical maintenance needs, including functionality tests, lubrication, and vibration monitoring. The findings emphasise the value of early failure detection through daily inspections and condition monitoring to support preventive and predictive maintenance approaches. Risk management plays a vital role in strategy selection, with risk assessments guiding the prioritisation of maintenance tasks. The limited application of failure mode, effects, and criticality analysis (FMECA) suggests room for improvement. This research underscores the need for a holistic maintenance approach that integrates proactive practices and risk management, offering a foundation for future studies of advanced maintenance strategies in refineries.